ANALISIS PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yeremy Sianipar; Anna Simbolon; Saran Raj; E Hamonangan Siallagan (Lembaga Pengembangan Kinerja Dosen, 2025)
The capital market is a place where investors buy and sell long-term securities, such as stocks and bonds. The capital market as a large place with many sellers and buyers interacting, determines the price of securities based on supply and demand. The purpose of the study was to determine whether the ratio of return on equity and return on assets partially and simultaneously have a significant effect on stock prices. The method used is regression analysis with a quantitative approach. The results of the study indicate that ROA and ROE have a positive effect on stock prices in coal companies listed on the Indonesia Stock Exchange (IDX).